Tiga Faktor Penghambat Pengembangan Bisnis Pada Pedagang Muslim di Pasar Ikan Hias Gungsari Surabaya - Kumara, Amri (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This research aims to determine the hindering factors that influence bussiness growth of Moslem vendors at Pasar Ikan Hias Gunungsari Surabaya.This research used quantitative methods through exploratory factor analysis.Characteristic of the population in this research are Moslem vendors at Pasar Ikan Hias Gunungsari Surabaya that have been active for at least a year. The number of samples at the time required 105 respondents. The sampling technique used is probability sampling. Sampling was done using simple random sampling.Results of the study indicate that there are three hindering factors that influence bussiness growth on Moslem vendors at Pasar Ikan Hias Gunungsari Surabaya. The three factors are the result of reduction of factor analysis processing. These three factors namely are unpreparedness to compete, lack of motivation, and limited funding.Suggestions for the government as the managing party of Pasar Ikan Hias Gunungsari Surabaya are holding meetings as a mean of discussion and hearing, encouraging entrepreneurial soul of the vendors, and improving the performance of the Building Society. It is suggested for Moslem vendors to join Moeslem entrepreneur community. Further research may focus on these factors influences toward other variables, such as the supporting factor that influences business growth. Moreover, further studies may also enlarge the scope of the research.